In Pursuit of Animal Justice: Review of The Three Ethologies (2024) by Matthew Calarco - Castelló, Pablo P. (Humanimalia, 2025)
Review of: Matthew Calarco, The Three Ethologies: A Positive Vision for Rebuilding Human–Animal Relationships. Animal Lives. Chicago: University of Chicago Press, 2024. 135 pp. 24.00 (pb).